Flood Aid Distribution Management System - Mohammad Syafiq Izzuan, Sabri (Universiti Malaysia Sarawak (UNIMAS), 2023)
Floods are a common natural disaster that can cause significant damage and displacement of people. An effective flood aid distribution management system is crucial in providing timely and efficient assistance to affected communities. The purpose of this project is to design and develop a flood aid distribution management system. The system will assist the Goods Charity Hub (GCH) Distribution Centre that is located in Selangor in managing the aid inventory, donor’s data, and Non-Governmental Organization (NGO)’s data effectively. Donors, NGOs, and the distribution center all play a critical role in the flood aid distribution management system. In this project, a donor, and an NGO act as different entities. A donor in this project context is a person or organization that donates aid to a distribution center, while an NGO is an organization that receives aid from a distribution center. A distribution center is the place where managing aids are performed. A literature review of existing applications was conducted to study the design, features, and functionality implemented in similar systems. The system will streamline the aid distribution process, improve the coordination and communication among stakeholders, and increase the transparency and accountability of the aid distribution process.